Genetic Correlates of Spirituality/Religion and Depression: A Study in Offspring and Grandchildren at High and Low Familial Risk for Depression - Anderson, Micheline R. (Spiritual Clin Pract (Wash D C ), 2017)
RATIONALE: Possible genetic correlates of spirituality and depression have been identified in community samples. We investigate some of the previously identified candidates in a sample of families at both high and low-risk for depression. METHOD: Offspring and grandchildren of individuals at high and low-risk for depression, participating in a multi-wave thirty-year longitudinal study, were assessed for seven SNPS drawn from four single gene candidates associated with systems implicated in both depression and spirituality: Serotonin (5-HT1B and 5-HT2A), Dopamine (DRD2), Oxytocin (OT) and Monoamine Vesicular Transporter (VMAT1). RESULTS: Dopamine (DRD2) Serotonin (5-HT1B), their Transporter (VMAT1) and Oxytocin (OXTR) were positively associated with a high level of importance of spirituality or religion (S/R) in the group at low familial risk for depression. DRD2 minor allele was associated with both lifetime major depressive disorder (MDD) and spirituality in the low-risk group for depression. No SNPs were related to S/R in the group at high familial risk for depression. OXTR was associated with lifetime MDD in the full sample. CONCLUSION: Genes for dopamine, serotonin, their vesicular transporter, and oxytocin may be associated with S/R in people at low familial risk for depression. Genes for dopamine may be associated both with S/R and increased risk for depression in people at low-risk for depression, suggesting a common pathway or physiology to mild to moderate depression. MDD is associated with oxytocin across risk groups. In the high-risk group, phenotypic expression of S/R may be suppressed. IMPLICATIONS: The shared association of DRD2 by S/R and depression, generally found to be inversely related, calls for further research on their common physiological pathways, and the phenotypic expression of these pathways based upon use and environment. Prevention for offspring at high familial risk for depression might include support for the development of child spirituality.